Tax Planning, Company Size, Profit Management, and Profitability as Moderating Variables - Tifani Ulfa; Rudi Zulfikar; Agus Sholikhan Yulianto (PT. EQUATOR SINAR AKADEMIA, 2022)
The purpose of this study was to determine the effect of tax planning, and firm size on earnings management moderated by profitability. The theory that is used as the basis for this research is agency theory. This study uses manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2021. The data used is secondary data. The results of this study indicate that tax planning and firm size have a significant effect on earnings management. Firm size affects earnings management moderated by profitability. While tax planning has no effect on profit management moderated by profitability